Using Ant-Word Profiler App to Classify Vocabulary Level for Paragraph Writing among EFL Learners - Agus Tina Sari; Dihliza Basya; Endah Nur Tjendani (English Teaching Journal : A Journal of English Literature, Language and Education, 2022)
There is a vast amount study of vocabulary assessment strategies by professional educators and a number of methods have emerged to gauge vocabulary competence. However, only a limited number of literatures analyze the use of online application to assess EFL students’ vocabulary level, especially in Indonesia. To fill this gap, this study employs Ant-Word Profiler App to classify students’ vocabulary level on final exam in advanced paragraph writing course among Indonesian undergraduate EFL Learners. Drawing on the Laufer Theory (1997) on factors which affect vocabulary learning, this study showcases the group of participants challenge their vocabulary mastery as they were routinely engaged to the writing class. The participants were, second semester students at Indonesia tertiary Institution who enrolled in Advanced Paragraph Writing course range from 19 to 22 years old. This descriptive interview study utilized a corpus-based research in vocabulary context of writing course. The AntWordProfiler app generates lexicon statistics and recurrence about the corpus of the text. The primary categories of the data collected are the overall quantity of running words in a apecific content of the given text. The results demonstrate that students at different stages of writing proficiency used a low percentage of Advanced vocabulary indeed on the final exam of the course. The implication of this study calls for the interactive vocabulary and writing pedagogy to enrich vocabulary mastery for students of language teacher education.